2000
DOI: 10.1002/etc.5620190209
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and dose rate estimates of 134137cesium and 90strontium in small mammals at chornobyl, Ukraine

Abstract: Free‐ranging mammals near the Chornobyl nuclear reactor are experiencing substantial radiation dose rates from intramuscular concentrations of 134137Cs and skeletal 90Sr. Radiocesium concentrations averaged 3,200 Bq/g of dry muscle, compared to a mean of 297 Bq 90Sr/g in bone for mammals in the Exclusion Zone, a region of restricted human activity surrounding the reactor. Estimates of dose rates from intramuscular sources of radiocesium averaged 2.4 mGy/d within 8 km of the reactor and ranged as high as 60 mGy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 21 publications
(31 reference statements)
2
9
0
1
Order By: Relevance
“…Hence, rather than any specific radioresistance (Shuryak, 2020), it is most likely that the tree-dwelling lifestyle of A. argenteus helps them to escape most external radiation exposure, resulting in a lack of association between their gut microbiota and soil radionuclide contamination (Figure 4). It is important to note that our estimates of external radiation dose for A. argenteus are extrapolated from experimental TLD data on soildwelling rodents (see Table S3; and Beresford et al, 2008;Chesser et al, 2000;Lavrinienko et al, 2020). Data from TLDs fitted on A. argenteus are required to quantify the effect of species-specific variation in space use on radiation exposure Shuryak, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, rather than any specific radioresistance (Shuryak, 2020), it is most likely that the tree-dwelling lifestyle of A. argenteus helps them to escape most external radiation exposure, resulting in a lack of association between their gut microbiota and soil radionuclide contamination (Figure 4). It is important to note that our estimates of external radiation dose for A. argenteus are extrapolated from experimental TLD data on soildwelling rodents (see Table S3; and Beresford et al, 2008;Chesser et al, 2000;Lavrinienko et al, 2020). Data from TLDs fitted on A. argenteus are required to quantify the effect of species-specific variation in space use on radiation exposure Shuryak, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…External radiation exposure (absorbed dose) of mice was estimated from the ambient radiation dose rate levels (radionuclide contamination of the environment, typically measured using a hand‐held Geiger counter) at trapping locations (Table ). This approach has been experimentally verified using implanted thermoluminescent dosimeters (TLDs) that directly measure absorbed external radiation dose rate in vivo (Beresford et al, 2008; Chesser et al, 2000; Lavrinienko et al, 2020). We also conducted a capture–mark–recapture pilot study and implanted TLDs ( n = 10, CHP Dosimetry) in A .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…comm). Studies on the accumulation of radionuclides in small mammals within this area in the late 1990s suggested that chronic dose rates could be as high as 86 mGy/day for the duration of their lifecycle (Chesser et al, , ). Similarly, many of the studies demonstrating genetic effects in scots pine are based on trees receiving doses orders of magnitude higher than the present study (Kuchma, Vornam, & Finkeldey, ; Vornam, Arkhipov, & Finkeldey, ), though effects at lower doses have also been recorded (Geras'kin & Volkova, ; Volkova, Geras'kin, & Kazakova, ).…”
Section: Discussionmentioning
confidence: 99%
“…De même, les animaux qui se nourrissent par fouissage comme les sangliers dans les forêts d'Autriche (Strebl et Tataruch, 2007) ou du sud de l'Allemagne (Semizhon et al, 2009) ou qui se nourrissent de lichens comme les rennes en Norvège (Anttila et al, 2011 ;Rasilainen et Rissanen, 2014) peuvent être fortement contaminés par le 137 Cs. De plus, il a été clairement montré que les rongeurs et les chauves-souris vivant dans la zone d'exclusion de Tchernobyl sont contaminés sur le long terme par un mélange de radionucléides, essentiellement 137 Cs et 90 Sr (Chesser et al, 2000 ;Chesser et al, 2001 ;Gashchak et al, 2010), tout comme les sangliers qui présentent une contamination mixte en 137 Cs et en 90 Sr et de niveau variable selon les zones de capture autour de Tchernobyl (Gulakov, 2014). Le 134 Cs, émetteur gamma comme le 137 Cs, fait également partie de ce mélange.…”
Section: Les Voies D'exposition Radiologique Des Populations En Situation Post-accidentelleunclassified